The Application of the RME Approach to Improve Students' Mathematical Concepts Understanding - Rina Febriana (Tarbawi : Jurnal Ilmu Pendidikan, 2021)
Learning mathematics less favored by students is a severe problem. This study aimed to improve mathematics learning outcomes in terms of mathematical concepts understanding using the RME approach. The research design used is quasi-experimental, with a pretest-posttest control group design. The data analysis technique used is the t-test. The population in this study is the third-grade students of SD Muhammadiyah Nitikan (Munita) Yogyakarta, Indonesia, with a sample of 10 students whose learning process is carried out online. The data was collected through a test of mathematical concepts understanding. The data were analyzed descriptively to determine the improvement of the average of mathematical concepts understanding. Based on the results of data analysis, the average initial score was 38.70, and the final test was 75.30. This result increases students' ability to understand mathematical concepts using the RME approach.